Emerging Complexity and the Need for Advanced Drug Delivery in Targeting Candida Species - Wadhwa, Ridhima; Pandey, Parijat; Gupta, Gaurav; Aggarwal, Taru; Kumar, Nitesh; Mehta, Meenu; Satija, Saurabh; Gulati, Monica; Madan, Jyotsna R.; Dureja, Harish; Balusamy, Sri R.; Perumalsamy, Haribalan; et al. (Current Topics in Medicinal Chemistry, 2019)
Background: Candida species are the important etiologic agents for candidiasis, the most prevalent cause of opportunistic fungal infections. Candida invasion results in mucosal to systemic infections through immune dysfunction and helps in further invasion and proliferation at several sites in the host. The host defence system utilizes a wide array of the cells, proteins and chemical signals that are distributed in blood and tissues which further constitute the innate and adaptive immune system. The lack of antifungal agents and their limited therapeutic effects have led to high mortality and morbidity related to such infections. Methods: The necessary information collated on this review has been gathered from various literature published from 1995 to 2019. Results: This article sheds light on novel drug delivery approaches to target the immunological axis for several Candida species (C. albicans, C. glabrata, C. parapsilosis, C. tropicalis, C. krusei, C. rugose, C. hemulonii, etc.). Conclusion: It is clear that the novel drug delivery approaches include vaccines, adoptive transfer of primed immune cells, recombinant cytokines, therapeutic antibodies, and nanoparticles, which have immunomodulatory effects. Such advancements in targeting various underpinning mechanisms using the concept of novel drug delivery will provide a new dimension to the fungal infection clinic particularly due to Candida species with improved patient compliance and lesser side effects. This advancement in knowledge can also be extended to target various other similar microbial species and infections.
Keywords: Immune-compromised patients